SISTEM EKONOMI BERDASARKAN KOPERASI DALAM KONSTITUSI: MENGGALI PEMIKIRAN KOPERASI HATTA - M Sofyan Pulungan (Arena Hukum, 2019)
AbstractOne of Mohammad Hatta's contributions to Indonesia was the selection of an economic system based on cooperatives as contained in Article 33 paragraph (1) of the 1945 Constitution of NRI. Hatta's thinking about cooperatives is still very relevant which was proven by the use of the rationale in the Constitutional Court Decision No .28 / PUU-XI / 2013 regarding the request for a judicial review of Law No. 17 of 2012 concerning Cooperatives. This study aims to determine what influences are believed to have contributed to the thinking of the Hatta cooperative. This study uses normative legal research methods with a historical approach. The results of the study found 3 (three) main influences for Hatta's cooperative thinking, namely: first economic and political thinking developed in Europe when Hatta settled there, secondly, the influence of the implementation of the colonial economic system by the Dutch East Indies Government. Third, the influence of the customs of the Indonesian people who have conformity with the values and principles of cooperatives.Â AbstrakSalah satu sumbangan pemikiran Mohammad Hatta bagi Indonesia adalah dipilihnya sistem ekonomi berdasarkan koperasi sebagaimana yang terdapat dalam Pasal 33 ayat (1) UUD NRI Tahun 1945. Pemikiran Hatta mengenai koperasi masih sangat relevan, hal ini dibuktikan dengan digunakannya landasan pemikiran tersebut dalam Putusan Mahkamah Konstitusi No.28/PUU-XI/2013 atas permohonan uji materiil Undang-Undang No.17 Tahun 2012 Tentang Perkoperasian. Penelitian ini bertujuan untuk mengetahui pengaruh-pengaruh apa saja yang diyakini telah memberikan kontribusi bagi pemikiran koperasi Hatta. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan historis (historiscal approach). Hasil penelitian menemukan 3 (tiga) pengaruh utama bagi pemikiran koperasi Hatta, yaitu: pertama pemikiran ekonomi dan politik yang berkembang di Eropa selama Hatta menetap di sana, kedua, pengaruh penerapan sistem ekonomi kolonial oleh Pemerintahan Hindia Belanda. Ketiga, pengaruh adat istiadat masyarakat Indonesia yang memiliki kesesuaian dengan nilai dan prinsip koperasi.Â